Pengukuran Hasil Belajar Mata Kuliah Agama Islam Berbasis Multiple Intelligence di Universitas Raharja Tangerang - Sudaryono, Sudaryono; Mukhtarom, Asrori; Abdurrohman, Asep (UNIVERSITAS RAHARJA, 2025)
Islamic Religious Education held at Higher Education in Indonesia generally has the same problem, namely the lack of methodology in learning so that it is less interesting. For this reason, innovation is needed in Islamic Religious Education. One solution is to use multiple intelligences-based learning. The formulation of the problem in this study is: 1. Is there a direct or indirect influence between kinesthetic intelligence, visual-spatial intelligence and language intelligence mediated by mathematical intelligence on the results of learning Islamic Religious Education at Raharja University in Tangerang? 2. Is there a direct or indirect influence between interpersonal intelligence, intrapersonal intelligence and existential intelligence mediated by naturalist intelligence on the results of learning Islamic Religious Education at Raharja University in Tangerang? This study is a quantitative study using the Smart-PLS Version 4.0 application for data analysis. The results of the study are: 1. Based on the results of the analysis, the R Square value of 0.651 was obtained for language intelligence, indicating that 65.1% of the variation in this variable can be explained by kinesthetic intelligence and visual-spatial intelligence in the model, with 34.9% influenced by external factors. This can be explained that the results of learning Islamic religion at Raharja University are influenced by language intelligence supported by kinesthetic intelligence and visual-spatial intelligence which are significant even though there are external factors on learning outcomes.2. Likewise, the R Square value of 0.646 for mathematical intelligence indicates that 64.6% of the variation in this variable can be explained by kinesthetic intelligence and visual-spatial intelligence in the model, with 35.5% influenced by external factors. From these results, it can also be said that the results of studying Islamic religion at Raharja University students have a significant influence on mathematical intelligence mediated by kinesthetic intelligence and visual-spatial intelligence. It can be said that there is a positive correlation between the three intelligences. 3. Based on the results of the analysis, the R Square value of 0.806 for existential intelligence indicates that 80.6% of the variation in this variable can be explained by intrapersonal intelligence and interpersonal intelligence in the model, with 19.4% influenced by external factors. Likewise, the R Square value of 0.697 for naturalist intelligence indicates that 69.7% of the variation in this variable can be explained by intrapersonal intelligence and interpersonal intelligence in the model, with 31.3% influenced by external factors.